Martin Scorsese and the American dream - Cullen, Jim, 1962- (Rutgers University Press, 2021)
More than perhaps any other major filmmaker, Martin Scorsese has grappled with the idea of the American Dream. His movies are full of working-class strivers hoping for a better life, from the titular waitress and aspiring singer of Alice Doesn't Live Here Anymore to the scrappy Irish immigrants of Gangs of New York. And in films as varied as Casino, The Aviator, and The Wolf of Wall Street, he vividly displays the glamour and power that can come with the fulfillment of that dream, but he also shows how it can turn into a nightmare of violence, corruption, and greed. This book is the first study of Scorsese's profound ambivalence toward the American Dream, the ways it drives some men and women to aspire to greatness, but leaves others seduced and abandoned. Showing that Scorsese understands the American dream in terms of a tension between provincialism and cosmopolitanism, Jim Cullen offers a new lens through which to view such seemingly atypical Scorsese films as The Age of Innocence, Hugo, and Kundun. Fast-paced, instructive, and resonant, Martin Scorsese and the American Dream illuminates an important dimension of our national life and how a great artist has brought it into focus.